2002
DOI: 10.1016/s0735-1097(02)02305-7
|View full text |Cite
|
Sign up to set email alerts
|

Determinants and prognostic value of left atrial volume in patients with dilated cardiomyopathy

Abstract: In patients with DCM, LA volume is associated with LV remodeling, diastolic dysfunction, and the degree of MR. The maximal volume of the LA has an independent and incremental prognostic value, compared with all its determinants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
206
1
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 320 publications
(217 citation statements)
references
References 31 publications
6
206
1
4
Order By: Relevance
“…In a previous study by Christiaens et al [17], the LAVmax, LAVmin and LAEF were measured using 64-MSCT, but the other left atrial functional variables were not evaluated. The left atrial function is impaired in a number of cardiovascular outcomes [2][3][4][5][18][19][20]. With abnormal LV relaxation, the relative contribution of the LA reservoir and the LA contractile function increases, and the conduit function decreases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study by Christiaens et al [17], the LAVmax, LAVmin and LAEF were measured using 64-MSCT, but the other left atrial functional variables were not evaluated. The left atrial function is impaired in a number of cardiovascular outcomes [2][3][4][5][18][19][20]. With abnormal LV relaxation, the relative contribution of the LA reservoir and the LA contractile function increases, and the conduit function decreases.…”
Section: Discussionmentioning
confidence: 99%
“…The principal function of the LA is to modulate left ventricular (LV) filling and the cardiovascular performance. It has been demonstrated that changes in the LA size and function are closely related to such cardiovascular diseases as diastolic dysfunction, cardiomyopathy, ischemic heart disease and valvular disease, and these changes act as barometers of cardiovascular outcomes [2][3][4][5][6]. The LA size and function are important factors in the development of atrial fibrillation and for determining the long term results of cardioversion.…”
Section: Introductionmentioning
confidence: 99%
“…The greater left atrial diameter seems to reflect reduced left ventricular compliance, but in this respect, it has been previously reported that the left atrial diameter is associated with the prognosis of patients with dilated cardiomyopathy or hypertrophic cardiomyopathy. 13,14 In hypertensive patients, particularly hypertensive men, it has been reported that the left atrial diameter correlates with the degree of obesity and the left ventricular myocardial mass, 15 and serves as a predictor of the risk of stroke or atrial fibrillation. 16,17 However, in the present study, in which data at a single point in time were analyzed, it is not possible to discuss the relationship of these parameters to prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…It is associated with an increased risk of death in patients with dilated cardiomyopathy, LV dysfunction and postmyocardial infarction [33,88,89,90]. Interestingly, in a study of 273 patients with heart failure (age 62 ± 9 years and 13% female) who underwent echocardiographic analysis and exercise testing with VO 2 max determination, LA volume normalized for body surface area (LAV/BSA) was strongly associated with mortality (HR 1.027 and 95% CI 1.018-1.04; p < 0.0001).…”
Section: La: a Marker Of Adverse Prognosismentioning
confidence: 99%